Mapping Cultural Influence on Green Economic Development - Lyulyov Oleksii; Pimonenko Tetyana (Economics and Culture, 2025)
This study explores the cultural underpinnings of green economic development in the EU and Ukraine by examining how national cultural dimensions shape eco-efficiency trajectories, institutional responsiveness, and technological transformation. By integrating Hofstede’s cultural framework with the Malmquist‒Luenberger productivity index (MLPI), this paper aims to identify cultural configurations that either catalyse or constrain green productivity and map country-specific patterns in green economic performance.